2020
DOI: 10.13181/mji.oa.204088
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to pain management adequacy in patients receiving palliative care: data from a tertiary hospital in Indonesia

Abstract: BACKGROUND Adequate pain management must be applied to improve the quality of life, particularly in patients receiving palliative care. Thus, this study aimed to determine the factors related to pain management adequacy in patients receiving palliative care. METHODS This cross-sectional study included all patients sent for consultation to the palliative care team complaining of pain in Cipto Mangunkusumo Hospital, Jakarta, Indonesia from 2016 to 2018. All data such as gender, age, employment status, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Included studies 16,17,24,25,5387 were published from 1999 to 2022 across 16 countries, with most studies conducted in Asia or Australia ( n = 26), followed by Europe ( n = 9) and the Americas ( n = 4). Twenty-three were prospective studies and 16 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included studies 16,17,24,25,5387 were published from 1999 to 2022 across 16 countries, with most studies conducted in Asia or Australia ( n = 26), followed by Europe ( n = 9) and the Americas ( n = 4). Twenty-three were prospective studies and 16 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included a mix of primary cancers, while six investigated a particular type of cancer. 61,68,74,81,83,87 Most studies reported discrimination measures, while two studies reported good calibration using the Hosmer-Lemeshow test ( p > 0.05) 65,85 and calibration plot ( R 2 = 0.799, p < 0.001). 85 Only one study reported reclassification measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, an abbreviated form of the Palliative Prognostic Index that simplifies the diagnosis of delirium was found to be predictive for patients with advanced cancer in a home hospice setting in South Korea [29]. Studies in Asian countries generally show good and comparable prognostic accuracy between the Palliative Prognostic Index and other systems or clinical prediction in predicting short-term survival in acute or palliative ward settings across various cancer types [19,23,[28][29][30][31][32][33][34].…”
Section: Palliative Prognostic Indexmentioning
confidence: 99%